Ta có \(\frac{6}{5}-\frac{1}{4}+\frac{4}{5}-\frac{3}{4}+\frac{1}{2}\)
\(=\left(\frac{6}{5}+\frac{4}{5}\right)-\left(\frac{1}{4}+\frac{3}{4}\right)+\frac{1}{2}\)
\(=2-1+\frac{1}{2}\)
\(=1+\frac{1}{2}\)
\(=\frac{3}{2}\)
\(\frac{6}{5}-\frac{1}{4}+\frac{4}{5}-\frac{3}{4}+\frac{1}{2}\)
\(=\left(\frac{6}{5}+\frac{4}{5}\right)-\left(\frac{1}{4}+\frac{3}{4}\right)+\frac{1}{2}\)
\(=\frac{10}{5}-\frac{4}{4}+\frac{1}{2}\)
\(=2-1+\frac{1}{2}\)
\(=1+\frac{1}{2}=\frac{3}{2}\)
Ghép cặp đi 6/5 với 4/5 và 1/4 với 3/4 ( nhớ chú ý dấu nha)
6/5 - 1/4 + 4/5 - 3/4 + 1/2
= (6/5 + 4/5) + (-1/4 - 3/4) + 1/2
= 2 - 1 + 1/2
= 1 + 1/2
= 3/2